Neuroökonomik, Institutionen und verteilte Kognition: Empirische Grundlagen eines nicht-reduktionistischen naturalistischen Forschungsprogramms in den Wirtschaftswissenschaften - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
– This paper presents an overview of recent research in neuroeconomics, in the light of the question how these relate to institutional economics. I present a critique of Glimcher's recent internalist standard model of neuroeconomics and put forward the claim that only an externalist approach can provide a consistent framework for relating neuroscience and economics, which implies a pivotal role for institutions. I discuss the relation between neuroeconomics and institutional economics from three different perspectives. How does neuroeconomics improve our knowledge about the relation between behavior and institutions (rule follwoing)? Can neuroeconomics provide deeper insights into the effects of institutions on behavior? In which way does neuroeconomics change the relation between institutional analysis and welfare analysis? In all these respects, I show that the orginal Hayekian conjectures applies, namely that the analysis of the human brain contributes substantially to our understanding of institutions, and that mental phenomena cannot be isolated from institutional phenomena.
Keywords: B41; B52; D02; D87; 330; neuroeconomics; institutions; multiple selves; identity; rule following; distributed cognition; imitation